2014
DOI: 10.1007/s10534-014-9793-9
|View full text |Cite
|
Sign up to set email alerts
|

Conserved metallomics in two insect families evolving separately for a hundred million years

Abstract: Μetal cofactors are required for enzymatic catalysis and structural stability of many proteins. Physiological metal requirements underpin the evolution of cellular and systemic regulatory mechanisms for metal uptake, storage and excretion. Considering the role of metal biology in animal evolution, this paper asks whether metal content is conserved between different fruit flies. A similar metal homeostasis was previously observed in Drosophilidae flies cultivated on the same larval medium. Each species accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…However, comparing concentrations, it has been reported that Zn, Cu and Mn concentrations may vary between Tephritidae (fruit flies) species fed with their regular diet. In addition those parameters can be changed by modification of regimen (Rempoulakis et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, comparing concentrations, it has been reported that Zn, Cu and Mn concentrations may vary between Tephritidae (fruit flies) species fed with their regular diet. In addition those parameters can be changed by modification of regimen (Rempoulakis et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Good yielding diets showed relatively low egg to pupa recovery (around 3% to 7%), but good pupal weight that developed into adults. The D. ciliatus egg-pupal efficacy, although relatively low, is comparable with the production of other tephritid fruit flies for which the development of diets has been particularly difficult, such as olive fly, Bactrocera oleae (Dimou et al, 2010;Rempoulakis et al, 2014b), and is probably related to the oligophagous nature of this fly (Rempoulakis et al, 2014a). A future research task will be of course to increase the yield of the diet and the observed eggpupa recovery for a viable mass rearing system towards SIT application against D. ciliatus.…”
Section: Discussionmentioning
confidence: 93%
“…These differences between the human and Drosophila enzyme support the hypothesis of evolutionary adaptation of these enzymes to distinct subcellular environments. Interestingly, Zn 2+ and Fe 2+ are both present in Drosophila at relatively high levels [35]. They are essential for Drosophila development and physiology and known to be specifically transported to the Golgi compartment [36, 37], which indicates that these metal ions are reasonable candidates for endogenous cofactors of DmCSAS.…”
Section: Discussionmentioning
confidence: 99%